2017
DOI: 10.1186/s12938-017-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of small-diameter decellularized scaffolds for vascular tissue engineering in an animal model

Abstract: BackgroundThe development of a suitable extracellular matrix (ECM) scaffold is the first step in vascular tissue engineering (VTE). Synthetic vascular grafts are available as an alternative to autologous vessels in large-diameter arteries (>8 mm) and medium-diameter arteries (6–8 mm). In small-diameter vessels (<6 mm), synthetic vascular grafts are of limited use due to poor patency rates. Compared with a vascular prosthesis, natural tissue ECM has valuable advantages. Despite considerable progress in recent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
(90 reference statements)
1
31
0
Order By: Relevance
“…Over the past decade, several groups have demonstrated the feasibility of completely acellular, off-the-shelf grafts in various animal models as well as human clinical trials. Decellularized and devitalized tissue-engineered constructs have been utilized with increasing frequency and have demonstrated improved patency and regeneration potential (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Devitalized constructs are based on bioengineered tissue constructs that are stripped of the cellular components while leaving extracellular matrix (ECM) components intact and then implanted into the animal model of choice (14).…”
mentioning
confidence: 99%
“…Over the past decade, several groups have demonstrated the feasibility of completely acellular, off-the-shelf grafts in various animal models as well as human clinical trials. Decellularized and devitalized tissue-engineered constructs have been utilized with increasing frequency and have demonstrated improved patency and regeneration potential (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Devitalized constructs are based on bioengineered tissue constructs that are stripped of the cellular components while leaving extracellular matrix (ECM) components intact and then implanted into the animal model of choice (14).…”
mentioning
confidence: 99%
“…For the scaffold choice, among the various possible approaches, ex vivo ‐ derived materials such as decellularized vessels have the structural and mechanical advantage of being composed of a native extracellular matrix (ECM) and possess bioactive molecules that aid tissue homeostasis and regeneration (Bejleri & Davis, ; Chen & Liu, ; M. C. Moore et al, ). Indeed, positive cell interactions with a structurally appropriate ECM aid and guide the regenerative response (Dahan et al, ; Uzarski, Van De Walle, & McFetridge, ; Xu et al, ). Clinical success of decellularized tissues has been reported in a range of applications, including trachea (Gonfiotti et al, ; Hamilton et al, ), heart valve (Dohmen, Lembcke, Holinski, Pruss, & Konertz, ; Tudorache et al, ), right ventricular outflow tract (Bibevski et al, ; Konertz et al, ) as well as vascular grafts (Olausson et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, positive cell interactions with a structurally appropriate ECM aid and guide the regenerative response (Dahan et al, 2017;Uzarski, Van De Walle, & McFetridge, 2013;Xu et al, 2017). Clinical success of decellularized tissues has been reported in a range of applications, including trachea (Gonfiotti et al, 2014;Hamilton et al, 2015), heart valve (Dohmen, Lembcke, Holinski, Pruss, & Konertz, 2011;Tudorache et al, 2016), right ventricular outflow tract (Bibevski et al, 2017;Konertz et al, 2011) as well as vascular grafts (Olausson et al, 2014(Olausson et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The decellularization method has been employed to simulate this complex structure effectively. To date, many groups have reported that transplanted decellularized ECM biomaterials loaded with different cell types improved myocardial function . However, the efficiency and long‐term viability still remains as a major challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many groups have reported that transplanted decellularized ECM biomaterials loaded with different cell types improved myocardial function. 9,10 However, the efficiency and long-term viability still remains as a major challenge. Therefore, the first step toward understanding the biology and physiology of transplanted cells is through documenting survival, homing, differentiation, and migration potential of these cells.…”
Section: Introductionmentioning
confidence: 99%